2008
DOI: 10.1016/j.yexcr.2007.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Lamellipodia nucleation by filopodia depends on integrin occupancy and downstream Rac1 signaling

Abstract: Time-lapse video-microscopy unambiguously shows that fibroblast filopodia are the scaffold of lamellipodia nucleation that allows anisotropic cell spreading. This process was dissected into elementary stages by monitoring cell adhesion on micropatterned extracellular matrix arrays of various pitches. Adhesion structures are stabilized by contact with the adhesive plots and subsequently converted into lamellipodia-like extensions starting at the filopodia tips. This mechanism progressively leads to full cell sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 45 publications
3
65
0
Order By: Relevance
“…2B). Both structures contain a large density of integrins (57) and play major roles in leading cancer cell migration and invasion (58,59). To study the cell morphological changes (lamellipodia and filopodia), a DIC microscope was used.…”
Section: Resultsmentioning
confidence: 99%
“…2B). Both structures contain a large density of integrins (57) and play major roles in leading cancer cell migration and invasion (58,59). To study the cell morphological changes (lamellipodia and filopodia), a DIC microscope was used.…”
Section: Resultsmentioning
confidence: 99%
“…4B). The effect of apigenin on filopodia formation may help to explain the effect on the directionality of cell movement, because inhibition of filopodia formation leads to impaired motility (41).…”
Section: And D)mentioning
confidence: 99%
“…Using substrates with discrete adhesion sites, Guillou et al (2008) [13] experimentally revealed the complex nature of membrane protrusion. First, filopodia grow until they reach an adhesion patch.…”
Section: Cell Environmentmentioning
confidence: 99%
“…substrate or matrix rigidity manipulation) [26], geometrically (e.g. shape and pitch length of adhesive pattern) [13] or topographically (3D adhesive structures with pillars or lines) [33,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation